Calcined Hydroxyapatite with Collagen I Foam Promotes Human MSC Osteogenic Differentiation - Hefka Blahnová, Veronika; Vojtová, Lucy; Pavliňáková, Veronika; Muchová, Johana; Filová, Eva (International journal of molecular sciences, 2022)
Collagen I-based foams were modified with calcined or noncalcined hydroxyapatite or calcium phosphates with various particle sizes and pores to monitor their effect on cell interactions. The resulting scaffolds thus differed in grain size, changing from nanoscale to microscopic, and possessed diverse morphological characteristics and resorbability. The materials' biological action was shown on human bone marrow MSCs. Scaffold morphology was identified by SEM. Using viability test, qPCR, and immunohistochemical staining, we evaluated the biological activity of all of the materials. This study revealed that the most suitable scaffold composition for osteogenesis induction is collagen I foam with calcined hydroxyapatite with a pore size of 360 ± 130 µm and mean particle size of 0.130 µm. The expression of osteogenic markers RunX2 and ColI mRNA was promoted, and a strong synthesis of extracellular protein osteocalcin was observed. ColI/calcined HAP scaffold showed significant osteogenic potential, and can be easily manipulated and tailored to the defect size, which gives it great potential for bone tissue engineering applications.
Keywords: kultivované buňky; bioceramics; tkáňové podpůrné struktury; Cell Differentiation; Tissue Engineering; osteogenesis; hydroxyapatit; Collagen Type I; kolagen typu I; Osteogenesis; Tissue Scaffolds; Cells, Cultured; osteogeneze; Humans; tkáňové inženýrství; Durapatite; collagen; buněčná diferenciace; lidé